Modulation of msl-2 5' splice site recognition by Sex-lethal. - Förch, P (2001)
The protein Sex-lethal (SXL) controls dosage compensation in Drosophila by inhibiting splicing and subsequently translation of male-specific-lethal-2 (msl-2) transcripts. We have previously shown that SXL blocks the binding of U2 auxiliary factor (U2AF) to the polypyrimidine (Py)-tract associated with the 3' splice site of the regulated intron. We now report that a second pyrimidine-rich sequence containing 11 consecutive uridines immediately downstream from the 5' splice site is required for efficient splicing inhibition by SXL. Psoralen-mediated crosslinking experiments suggest that SXL binding to this uridine-rich sequence inhibits recognition of the 5' splice site by U1 snRNP in HeLa nuclear extracts. We also show that SXL interferes with the binding of the protein TIA-1 to the uridine-rich stretch. Because TIA-1 binding to this sequence is necessary for U1 snRNP recruitment to msl-25' splice site and for splicing of this pre-mRNA, we propose that SXL antagonizes TIA-1 activity and thus prevents 5' splice site recognition by U1 snRNP. Taken together with previous data, we conclude that efficient retention of msl-2 intron involves inhibition of early recognition of both splice sites by SXL.